2022
DOI: 10.25259/sni_795_2022
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar epidural blood patch: An effective treatment for intracranial hypotension

Abstract: Background: The literature has demonstrated the efficacy of lumbar epidural blood patch (LEBP) in the management of spontaneous intracranial hypotension (SIH). However, the underlying pathophysiology of such management remains unclear. In this study, we aim to evaluate the utility of LEBP injections in the management of SIH and develop a potential management algorithm used in the triage and management of SIH patients. Methods: We retrospectively examined the clinical case notes of 14 patients with SIH (age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
0
0
Order By: Relevance
“…A limited-scale investigation involving the retrospective review of medical records from 14 patients diagnosed with SIH (aged 25-69 years) revealed that a single EBP injection resulted in symptom and radiological resolution in 85% of cases. Notably, 85% of patients experienced symptomatic improvement, with 64% achieving complete symptom resolution and 21% showing moderate improvement [31].…”
Section: Epidural Blood Patch (Ebp)mentioning
confidence: 99%
“…A limited-scale investigation involving the retrospective review of medical records from 14 patients diagnosed with SIH (aged 25-69 years) revealed that a single EBP injection resulted in symptom and radiological resolution in 85% of cases. Notably, 85% of patients experienced symptomatic improvement, with 64% achieving complete symptom resolution and 21% showing moderate improvement [31].…”
Section: Epidural Blood Patch (Ebp)mentioning
confidence: 99%